Prognostic implications of tumor-infiltrating lymphocytes in non-small cell lung cancer: a systematic review and meta-analysis - Yan, Qin; Li, Shuai; He, Lang; Chen, Nianyong (Frontiers in Immunology, 2024)
Background: Tumor-infiltrating lymphocytes (TILs) have demonstrated potential as prognostic biomarkers across various cancer types. However, their prognostic implications in non-small cell lung cancer (NSCLC) remain ambiguous. Methods: An exhaustive electronic search was executed across the Pubmed, EMBASE, Web of Science, and Cochrane Library databases to locate relevant studies published up until December 19, 2023. Studies were eligible if they assessed the association between TILs and overall survival (OS) and disease-free survival (DFS) in NSCLC patients. The OS and DFS were subsequently extracted for analysis. The prognostic significance of TILs was evaluated by calculating the Pooled Hazard Ratios (HRs) and their corresponding 95% Confidence Intervals (CIs). Results: The meta-analysis incorporated 60 studies, which collectively included 15829 NSCLC patients. The collective analysis indicated that NSCLC patients exhibiting TILs infiltration demonstrated a significantly improved OS(HR: 0.67; 95%CI: 0.55-0.81). Subgroup analyses, based on TIL subtypes (CD8+, CD3+ and CD4+), consistently revealed a favorable prognostic impact on OS. However, it was observed that FOXP3+ was correlated with a poor OS (HR: 1.35; 95% CI: 0.87-2.11). Conclusion: This comprehensive systematic review and meta-analysis substantiate the prognostic significance of TILs in patients diagnosed with NSCLC. Notably, elevated TILs infiltration correlates with a favorable prognosis, particularly among CD8+, CD3+ and CD4+ subtypes.